Properties of dilute weak charged solutions - Shikin, V. (Recent Contributions to Physics, 2015)
A neutral donor dissociation into charged fragments typical of electrolytes is one of the reversible reactions satisfying the law of mass action (LMA) [1]. Its application to weak electrolytes results into the formula (Ostwald law) for an important characteristic of the electrolyte, its ionization degree α [1, 2].
Keywords: Electrolyte solution ionization